Successful Organizational Transformation Strategy of PT Wijaya Karya (PERSERO) TBK - Yantama, Rian Rizki; Suroso, Arif Imam; Safari, Arief (International Journal Labs, 2026)
This study aims to examine the extent to which internal factors, external factors, transformation strategy, and organizational alignment influence the success of WIKA’s transformation agenda. An explanatory quantitative approach was employed using Structural Equation Modeling–Partial Least Squares (SEM-PLS), based on responses from 134 employees and structural officials directly involved in the transformation process. The study investigates five latent constructs: Internal Factors, External Factors, Transformation Strategy (sensing, seizing, and reconfiguring), Organizational Alignment (structural, process, cultural, and team-based consistency), and Transformation Success (financial and non-financial performance). Data analysis was conducted using SmartPLS through a comprehensive evaluation of both the measurement and structural models. The empirical results indicate that both internal and external factors serve as significant drivers of transformation strategy. Furthermore, transformation strategy exerts a substantial direct effect on organizational alignment, which functions as a critical mediating mechanism linking strategic direction to transformation success. Organizational alignment is also proven to have a strong direct impact on overall transformation performance, underscoring the importance of aligned structural design, cultural readiness, and human resource capabilities as prerequisites for successful change. This study enriches the theoretical discourse on organizational transformation in State-Owned Enterprises by integrating the perspectives of dynamic capabilities, strategic alignment, and change management. Practically, the findings offer actionable insights for WIKA and similar SOEs in formulating integrated, capability-oriented transformation roadmaps grounded in organizational culture.